2023
DOI: 10.28945/5072
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Big Data Management on Organizational Performance in Organizations: The Role of Electronic Records Management System Potentiality

Abstract: Aim/Purpose: The use of digital technology, such as an electronic records management system (ERMS), has prompted widespread changes across organizations. The organization needs to support its operations with an automation system to improve production performance. This study investigates ERMS’s potentiality to enhance organizational performance in the oil and gas industry. Background: Oil and gas organizations generate enormous electronic records that lead to difficulties in managing them without any system o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…More importantly, technology acceptance is deemed to determine successful product/technology adoption, and its examination from the user’s perspective can provide new information concerning the likes and dislikes of its various features, the product, and the user’s attitude toward it (Hawash et al, 2023; Mukred et al, 2023). Therefore, a systematic literature review on the topic must present a complete picture of the acceptance level of big data technology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, technology acceptance is deemed to determine successful product/technology adoption, and its examination from the user’s perspective can provide new information concerning the likes and dislikes of its various features, the product, and the user’s attitude toward it (Hawash et al, 2023; Mukred et al, 2023). Therefore, a systematic literature review on the topic must present a complete picture of the acceptance level of big data technology.…”
Section: Methodsmentioning
confidence: 99%
“…In the same line of research, Pancic´et al (2023) investigated the factors of big data analytics and block-chain adoption and their subsequent influence on firm performance, driven by the increasing popularity of business intelligence. This highlights the importance of BDA as a professional tool to be used by governments and organizations worldwide (Hawash et al, 2023;Mukred et al, 2022).…”
Section: Introductionmentioning
confidence: 96%
“…The studies of them showcased the pitfalls and benefits linked to the taught as online methods in higher institutions. [22] In their research, Hawash et al ( 2023) identified the impact of information management on the operational success of enterprises, specifically with regard to electronic records management systems. The studies highlighted the fact that big data analytics could be optimally used only if adequate data governance and the infrastructure were in place.…”
mentioning
confidence: 99%